Serial group rings of finite groups. General linear and close groups - Kukharev, A.; Puninski, G. (Algebra and Discrete Mathematics, 2015)
For a givenp, we determine when thepmodulargroup ring of a group from GL(n,q), SL(n,q) and PSL(n,q)-seriesis serial.